Dynamics of liquid imbibition through paper with intra-fibre pores. (20th April 2018) - Chang, Sooyoung; Seo, Jaedeok; Hong, Seokbin; Lee, Duck-Gyu; Kim, Wonjung
Abstract : We present a combined experimental and theoretical investigation of the dynamics of liquid imbibition through paper. The Washburn equation is widely used to describe the dynamics of capillary flow through paper, but this classical model has limited accuracy, which often makes it difficult to use in developing analytic systems such as paper-based microfluidic devices. We here report that the internal cavity of the cellulose fibres composing paper is significantly responsible for the limited accuracy of the Washburn equation. Our experiments demonstrated that liquid can be absorbed in the internal cavity of the cellulose fibres as well as in the inter-fibre pores formed by the fibre network. We developed a mathematical model for liquid imbibition by considering the flow through the intra-fibre pores based on experimental measurements of the intra-structure of cellulose fibres. The model markedly improves the prediction of the liquid absorption length, compared with the results of the Washburn equation, thus revealing the physics behind the limits of the Washburn equation. This study suggests that the accurate description of capillary imbibition through paper require parameters characterizing the internal pores of the cellulose fibres comprising the paper. Our results not only provide a new insight into porous media flows with different sized pores, but also provide a theoretical background for flow control in paper-based microfluidic systems.